South African peace mission personnel and sexual misconduct against women in the Democratic Republic of Congo: A Constructivist exploration of Norm Internalisation - Ogunrombi, Anjola (Department of Political Studies, 2020)
UN peace mission personnel sexual misconduct against women violates international norms and law, and persists despite the multitude of interventions aimed at combatting it. South African personnel have repeatedly been identified as perpetrators which calls into question whether the norms that prohibit such conduct have been internalised. Insufficient research has been conducted to interpret the relationships between the political dynamics of UN peace missions and the international norms that govern appropriate conduct towards women. By using a Constructivist lens to examine the mechanisms behind Norm Internalisation, and by analysing how this applies to South African personnel, this research identifies some of the reasons why South Africa’s apparent commitment to international norms about women does not always result in appropriate behaviour. The research examines the UN’s zero-tolerance policy and South Africa’s compliance therewith, demonstrating the challenges that the political dynamics between these two actors has in achieving Norm Internalisation. This research provides a foundation for future research on the topic of peacekeeper sexual misconduct by highlighting the role that norms can play in determining appropriate behaviour.